The role of local authorities in Malaysia toward safe cities initiative - Raja Othman, Raja Norashekin; Yussof, Farrah Norizzah; Adnan, Hamimah; Yaman, Rostam; Marzukhi, Marlyana Azyyati (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Local authorities in Malaysia are facing mounting challenges in managing and maintaining urban areas. City life is complex due to the interactions of people in crowded areas. The performance of local authorities greatly influences the public's impression of the entire governance system, and safe delivery is a key metric for gauging a developed nation's success. The role of local authorities in the Safe Cities initiative is crucial for ensuring the safety and well-being of residents. Local authorities play a significant role in implementing, managing, and overseeing various aspects of creating a safe and secure urban environment. Various strategies and signs have been implemented to ensure safety. It is crucial to understand the role of LAs and how they represent safety initiatives, as reflected in the Safe Cities index. Therefore, in this study, three (3) local authorities (LAs) at central zone were chosen as the case study and stated as CS1, CS2 and CS3. A qualitative methodology using semi- structured interviews was conducted to achieve both objectives. The aim of this paper is to have an overall view of safe city implementation conducted and to what extent the core business of each LA aligned with the five (5) key domains of safe city: personal (physical), infrastructure, digital, health and environment security. Besides, it identifies which domain captures the most dominant among the departments within the local authority level. Besides, it identifies which domain captures the most dominant among the departments within the local authority level. This study reveals that only about half of the departments in the case studies were aligned with the task of creating safe city initiatives. It was implemented in 11 out of 22 departments to address objective one. The local authority council commonly utilises the domain of digital security among its various departments to address the second objective. The research findings provide crucial new information for establishing appropriate benchmarks for safe cities to be delivered at all council levels. The findings from this study hold significant importance, serving as a guiding light for other local authorities (LAs) seeking suitable benchmarks in their pursuit of a safer city paradigm. It's evident that the approach adopted by these authorities extends beyond crime prevention within the physical realm, encompassing multiple facets across safe city domains. This collective effort underscores the progress of LAs in Malaysia's central zone, demonstrating advancement not solely within specific departments but across the board. The forthcoming study explores diverse initiatives and strategies that promise to curtail operational costs while enhancing community life quality—a pivotal exploration. Ultimately, this approach can be extrapolated to municipalities and districts nationwide by tailoring adjustments to suit specific local contexts, fostering widespread implementation and positive impact throughout Malaysia.